Comparative Performance of Apple (Malus×Domestica Borkh.) Cultivars For Various Horticultural Traits in Kullu Valley of Himachal Pradesh - Kumar, Lokender; Dogra, Rajesh Kumar; Bhatia, Hardev Singh; Chandel, Ashu (International Journal of Economic Plants, 2020)
The present investigation was carried out for the evaluation of twelve cultivars of apple namely Red Chief, Vance Delicious, Oregon Spur II, Super Chief, Scarlet Gala, Gale Gala, Red Delicious, Top Red, Scarlet Spur Red Delicious, Early Red One, Red Fuji and Gold Spur for their tree characters, time and duration of flowering, fruiting and chemical characteristics, during 2018-19 at Kullu valley of Himachal Pradesh. Red Fuji recorded maximum tree height (5.59 m) and minimum (2.96 m) in Super Chief. The maximum leaf area (38.57 cm2) was recorded in Early Red One. Time of full bloom was found earliest (3rd April) in Gale Gala and Scarlet Gala and latest (8th April) in Gold Spur. Fruit weight was found maximum (153.49 g) for Scarlet Spur Red Delicious and minimum (114.36 g) was observed in Red Fuji. Yield tree-1 was maximum (37.32 kg) in Red Delicious V-22 and minimum (21.59 kg) in Red Chief. Total sugars was maximum (12.50%) in Red Fuji and minimum (10.16%) in Gold Spur.